Inhibition and recovery of germination and growing ability of seedlings under and after osmotic stress induced by polyethylene glycol in 8 pea genotypes - Dobránszky, J.; Iszály-Tóth, J.; Magyar-Tábori, K. (International Journal of Horticultural Science, 2006)
Germination and early seedling growth of eight pea genotypes were examined under and soon after different (5%, 10%, 15%, and 20%) PEG treatments. Seeds were germinated on PEG solution for 3 or 6 days and then further germinated and cultured on filter paper moistened by water for 3 and 6 days. The length and fresh weight of shoots and roots of seedlings were measured and used for evaluation of genotypes. Roots were less inhibited by osmotic stress than shoots similarly to other plant species. The variability among the genotypes was the greatest in the case of shoot growth at 5% PEG treatment and in the case of root growth at 15% PEG treatment. Results suggest that growing responses of genotypes after cessation of stress are more suitable for the evaluation of their osmotic tolerance, than their responses expressed during in vitro stress conditions. Genotypes with relatively high or low osmotic stress tolerance, respectively, could be distinguished with 6 days after recovery from 3-day-long 15% PEG treatment concerning the rate of shoot weight to root weight.